Pemberdayaan Komunita Lansia: Pendidikan Gizi pada Sekolah Lansia SMART Kota Malang - Viantry, Paramita; Sargowo, Djanggan; Puspitarini, Marinda Dwi (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2025)
The nutritional issues faced by the elderly significantly affected the occurrence of non- communicable diseases (degenerative diseases), especially among elderly individuals with obesity. Education and nutrition training played an important role in preventing and managing these conditions through the promotion of balanced nutrition for the elderly. Nutritional education significantly reduced the risk of chronic diseases and increased individual awareness, particularly among the elderly, about the importance of implementing balanced nutrition. The main objective of this community service program was to enhance knowledge about balanced nutrition for the elderly to prevent and manage these conditions at the SMART Elderly School under the Abiyoso Gerontology Foundation in Malang City. The implementation of this community service activity included nutritional education using PowerPoint presentation materials, facilitating Focus Group Discussions (FGDs), conducting anthropometric measurements, and practicing the preparation of balanced nutritional menus for the elderly. Before and after the nutritional education, knowledge assessments regarding balanced nutrition for the elderly were conducted, with paired t-test analysis. The results showed significant data that improved the elderly's understanding of the causes, prevention, and management of non- communicable diseases. Therefore, the importance of regular activities in raising awareness among the elderly about the habit of applying balanced nutrition was highlighted.